2008
DOI: 10.1007/s11483-008-9080-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrophilic and Lipophilic Compounds on Zein Microstructures

Abstract: Zein, the prolamine of corn, contains nearly an equal amount of hydrophilic and lipophilic amino acid residues. Its tertiary structure has a regular geometry measuring 17×4.5×1.2 nm. The structure of zein allows it to function as a polymeric amphiphile. Zein had been observed to self-assemble into periodic bilayer structures and nanotubes. This work investigated the structural development of zein self-assemblies as affected by the hydrophilic-lipophilic balance (HLB) of the system. The formation of several str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 18 publications
4
37
0
2
Order By: Relevance
“…These films had a rough surface and the microparticles were poorly fused (arrows, Figure 2A-g, h), which was similar to the appearance of biomaterials made from zein microparticles such as films (22)(23) and sponges (24). Previous work has shown that films prepared from microwave-heated kafirin had a rough surface, which was attributed to Taylor (34) reported a reduction in α-helical conformation when they studied the protein secondary structure in cooked kafirin.…”
Section: A-c D)supporting
confidence: 51%
“…These films had a rough surface and the microparticles were poorly fused (arrows, Figure 2A-g, h), which was similar to the appearance of biomaterials made from zein microparticles such as films (22)(23) and sponges (24). Previous work has shown that films prepared from microwave-heated kafirin had a rough surface, which was attributed to Taylor (34) reported a reduction in α-helical conformation when they studied the protein secondary structure in cooked kafirin.…”
Section: A-c D)supporting
confidence: 51%
“…According to these authors the morphological changes in zein-oleic acid system occurred at three steps; (1) formation of large numbers of oleic acid coated zein spheres, (2) partial melting of the spheres by means of oleic acid, and (3) transformation of a sponge like morphology by interconnection of spheres with channels and tunnels. The spheres observed by SEM of zein-oleic acid films in this work lacked the interconnections specified by Wang et al (2008). Thus, it seemed that the lecithin emulsifier used in this work stabilized the oleic acid coating formed around zein spheres.…”
Section: Sem Analyses Of Zein Filmsmentioning
confidence: 67%
“…Thus, it seemed that the lecithin emulsifier used in this work stabilized the oleic acid coating formed around zein spheres. It appears that the repulsion formed by negative charges of lecithin at the oleic acid coating of formed zein spheres prevented the interaction and melting down of these spheres which formed the sponge-like structure described by Wang et al (2008). Thus, it appeared that the reduced release rates of lysozyme in catechin containing zein-oleic acid blend films are in part due to the entrapment of lysozyme within spherical capsules which increased the barriers against enzyme diffusion.…”
Section: Sem Analyses Of Zein Filmsmentioning
confidence: 98%
See 1 more Smart Citation
“…Wang et al (10) investigated the effect of various hydrophilic and lipophilic compounds on zein aggregation and selfassembly. This study revealed that lipophilic compounds increased the curvature of zein and thereby resulting in the development of smaller spherical particles.…”
Section: Introductionmentioning
confidence: 99%